A identidade do poeta contemporâneo à luz do sintagma identidade-metamorfose-emancipação - Gunutzmann, Pricila (2012)
This dissertation investigates the metamorphosis of the poet's contemporary identity and the meaning they attribute to their art as well as the perceived political positions in his role. For this, we start from the social psychology, with the main category of identity, seen from the syntagma identity-metamorphosisemancipation, to understand the phenomenon not only in its instrumental aspect, but the whole context in which the contemporary poet is inserted. Through the analysis of the life story of two poets of today, it was possible to understand the processes of transformation and emancipation of human identity in contemporary societies, which occurs in contexts permeated by the dialectic regulation/emancipation. This study examined the poet as a contemporary subject, able to interpolate opening times and disruptions so their reader can fill it in with their own experiences, providing metamorphoses. We went through the construction of the role of the poet in our society and their different historical characters: artist, politician and guardian of metamorphoses, verifying its relations with the present. Thus, this study sought to weave reflections about the different possibilities of emancipation in contemporaneity as well as provide insight to discuss the meanings of metamorphosis and post-conventional identities